Making money out of people's misery has disaster capitalism taken over post-Haiyan Philippines? - Porteria, April (Philippine Sociological Review, 2015)
In the age of neoliberal globalization, it is no longer surprising that even the most distressing situations can be a source of profit. The term "disaster capitalism" has been used to describe the global pattern of big businesses profiting from disasters. This was observed in the aftermath of Hurricane Katrina in the United States, Indian Ocean tsunami in South and Southeast Asia, and the Haiti earthquake. The aftermath of super typhoon Haiyan provides some indications of disaster capitalism at work. However, there are also distinct characteristics in the post-Haiyan case. This critical essay argues that disaster capitalism in the Philippines has specific nuances that mirror the pre-existing characteristics of the Philippine political economy, which is a combination of patronage politics and neoliberal policies. The article also highlights the role of people's movements in resistance and efforts of insulating the country from disaster capitalism.